Design and synthesis of new thiophene derivatives together with their antitumor evaluations - Mahmoud, Mahmoud Ali Abdelaziz (European Journal of Chemistry, 2015)
A series of new thiophene derivatives (3a,b) have been prepared by the reaction of acetylacetone with either cyanoacetanilide or 2-cyano-N-(p-tolyl)acetamide and elemental sulfur in the presence of triethylamine as basic catalyst. The two synthesized compounds were used to further synthesize new thiophene derivatives. The structures of all the newly synthesized products have been established on the basis of analytical and spectral data. The antitumor activity of the newly thiophene derivatives was evaluated against six human cancer cell lines, namely gastric cancer (NUGC), colon cancer (DLD1), liver cancer (HA22T and HEPG2), nasopharyngeal carcinoma (HONE1), breast cancer (MCF) and normal fibroblast cells (WI38).